Analisis pengaruh tinggi bilah terhadap performa dengan airfoil NACA 0012 pada turbin angin sumbu vertikal tipe darrieus-H di Jawa Barat - Raditya Elfa Pratama; Marno; Aripin (Jurnal Teknik Mesin Indonesia, 2023)
The wind turbine that has the best performance for urban areas with easy maintenance is the Darrieus-H Vertical Axis Wind Turbine (TASV). The purpose of this study was to determine the characteristics of the NACA 0012 airfoil, to determine the effect of blade height on TASV performance, and to obtain the optimum blade design. The method used in this research is the simulation and analysis method. Wind turbine simulations and analysis were carried out using Microsoft Excel software to process data, Rotor DMS Simulation on Qblade to determine airfoil characteristics and analyze wind turbine performance, and Ansys FLUENT to determine fluid flow that occurs in the blades. In this study, with regional conditions in West Java having an average wind speed of 6.83 m/s and a maximum wind speed of 10 m/s, simulations and analysis with several variations in height obtained the results that the Darrieus Vertical Axis Wind Turbine (TASV) blade H has the same maximum Coefficient Power (Cp), which is 73% at a TSR of 4.5. In the study, also with a 300 W generator, the optimum blade height was obtained, which has a design of 0.7–1.1 meters with a power generated of 99.8–492 W with a torque of 1.72–5.80 Nm at a rotor rotational speed of 55.05–85 rad/s.